Rice husk activated carbon with NaOH activation: physical and chemical properties - Mohamad Jani Saad; Chia, Chin Hua; Sarani Zakaria; Mohd Shaiful Sajab; Sufian Misran; Mohammad Hariz Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Activated carbon was produced from rice husk by activating with NaOH. Three types of samples were made at 850, 750, and 650 °C activation temperature. The properties of the samples were determined. The activated carbons have surface area of 429.82 m2 /g from 850 °C activation, 121.39 m2 /g (750 °C) and 93.89 m2 /g (650 °C). The results were higher than rice husk carbon without activation (0.23 m2 /g). The activated carbons have mesopore size (2-50 nm). Proximate and ultimate analyses of the samples were also determined. The activation process increased the carbon content of the samples. Physical characteristics of the activated carbons were shown from the XRD analysis. FTIR demonstrated the different functional of the rice husk carbon and activated. The SEM images showed the pores on the surface of the activated carbon due to the NaOH activation.